Comparative Study on the Use of the Educational Resources of PeruEduca by Teachers from Arequipa and Moquegua - Bejarano, Anyela (2020)
PeruEduca is an educational platform implemented by the Ministry of Education of Perú for providing free resources for teaching at different educational levels. This research presents the analysis of the use of PeruEduca in the teaching-learning process. This study began with a survey carried out with two groups of teachers belonging to the regions of Moquegua and Arequipa, using the criteria of mandatory Educational Quality Examination of the Ministry of Education, which is applied annually. The teachers are graduates of the master’s degree course in the management of virtual learning environments offered by the Catholic University of Santa María. The analysis was carried out considering two aspects: digital competencies and the teaching-learning process. The results of this survey indicate that students from the Moquegua region are having better performances in their learning than students of the Arequipa region. This difference could be attributed to the extensive use of digital resources from the PeruEduca platform in the teaching-learning process. Thus, teachers must be sensitized at the local level to reflect on their pedagogical practices and incorporate methodological strategies in which they can use virtual environments in the development of their learning sessions.